1993
DOI: 10.1182/blood.v81.10.2702.bloodjournal81102702
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent in situ hybridization and cytogenetic studies of trisomy 12 in chronic lymphocytic leukemia

Abstract: Cytogenetic studies (CG) of 475 chronic lymphocytic leukemia (CLL) cases showed trisomy 12 in 6.1% or 26% of patients with abnormal karyotypes. Fluorescence in situ hybridization (FISH) detected trisomy 12 in 35% of 117 CLL patients. Only 34.6% of cases detected by FISH were detected by CG. Twelve patients had low levels of trisomic cells (4% to 11%) relative to clonal B cells (47.5% to 86%), suggestive of clonal evolution. Untreated patients with trisomy 12 were predominantly male (P < .05) and had an incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In all studies that compared conventional chromosome banding techniques and interphase cytogenetics, the frequency of trisomy 12 was higher when assessed by FISH using DNA probes that recognized the repetitive sequences of the cen-tromeric and pericentromeric region. The frequencies of trisomy 12 in the FISH studies range from 10 to 20% in most European series, to more than 30% in two studies from the United States (86,88). This variation possibly results from patient selection; however, differences may also be due to a different geographical distribution of this chromosome aberration.…”
Section: Clinical Impact Of 11q22-q23 Deletion In Cllmentioning
confidence: 94%
See 1 more Smart Citation
“…In all studies that compared conventional chromosome banding techniques and interphase cytogenetics, the frequency of trisomy 12 was higher when assessed by FISH using DNA probes that recognized the repetitive sequences of the cen-tromeric and pericentromeric region. The frequencies of trisomy 12 in the FISH studies range from 10 to 20% in most European series, to more than 30% in two studies from the United States (86,88). This variation possibly results from patient selection; however, differences may also be due to a different geographical distribution of this chromosome aberration.…”
Section: Clinical Impact Of 11q22-q23 Deletion In Cllmentioning
confidence: 94%
“…Using restriction fragment length polymorphism (RFLP) studies, it was shown that trisomy 12 in CLL results from duplication of one homolog, rather than from loss of one homolog, and triplication of the remaining one (84). Trisomy 12 is the aberration most extensively studied by molecular cytogenetics in CLL (8,62,(85)(86)(87)(88)(89)(90)(91) (Table 1). In all studies that compared conventional chromosome banding techniques and interphase cytogenetics, the frequency of trisomy 12 was higher when assessed by FISH using DNA probes that recognized the repetitive sequences of the cen-tromeric and pericentromeric region.…”
Section: Clinical Impact Of 11q22-q23 Deletion In Cllmentioning
confidence: 99%
“…Our group and others have reported on numerical chromosome 12 abnormalities in chronic lymphocytic leukemia by using FISH (Perez-Losada et al, 1991;Anastasi et al, 1992;Cuneo et al, 1992;Qumsiyeh I 62 rourm ET AL. Escudier et al, 1993). In this paper, we report our findings on polysomy 12 in 60 consecutive evaluable cases of N H L with FISH.…”
Section: Introductionmentioning
confidence: 89%
“…A mild clinical course was observed in the remaining patient with 6p anomaly, which was apparently not in¯uenced by the presence of 12 in interphase cells. It is worth noting that, whereas 12 in metaphase cells has an unfavourable prognostic signi®cance compared with other single anomalies (Juliusson et al, 1991), the presence of 12 in interphase cells does not per se convey an inferior outcome (Escudier et al, 1993;Bentz et al, 1999). The relatively small size of the trisomic clone in these patients and its low in vitro mitotic index may partially account for this observation.…”
Section: Discussionmentioning
confidence: 99%